Impact of Technological Innovation on Quality Service Delivery in Nigerian Railway Corporation (2017 - 2021) - Onuorah, Onyeka Leo; Abdullahi, Bosso Umar; Mohammed, Ngozi Thelma (NIU Journal of Social Sciences, 2022)
The adoption of technological innovation in the Nigerian Railway Corporation has received amplified attention in recent times as it has been tested using various models. Experience in selected train stations indicates that innovative ideas have not been effectively and successfully implemented due to the nature and character of bureaucracy in the Nigeria Railway Corporation. Therefore, the study's objective is to examine the effect of technological innovation on the quality service delivery of Nigerian Railway Corporation using selected train stations in Nigeria. The hypothesis that guided the study is null and alternative; H o : Technological Innovation does not affect quality Service Delivery in Nigerian Railway Corporation. H 1 : Technological Innovation affects quality Service Delivery in Nigerian Railway Corporation. The study adopted Socio-Technical System Theory as a framework for theoretical analysis. A descriptive survey design was adopted as a research methodology—the collected data for the study through primary and secondary sources of data collection. The study population comprised 389 selected employees of the Nigerian Railway Corporation at Kaduna, Abuja, Lagos and Ibadan (train stations chosen for the study). Data obtained from the survey were analysed using Statistical Package for Social Science (SPSS) version 26. The study adopted descriptive statistics for Mean, and the test of hypotheses was done using correlation coefficient analysis. Findings from the study indicate that technological innovation has played a crucial role in progressing and developing railway administration in Nigeria. It has improved various aspects of the railway system. The study recommended that institutionalised corruption should be eliminated from the railway sector. Keywords: Technology, Innovation, Service Delivery, Public Corporation, Nigeria